Relative growth, sexual maturity, and breeding season of three species of the genus Persephona (Decapoda: Brachyura: Leucosiidae): A comparative study - Almeida, Ariádine Cristine; Hiyodo, Célia Mary; Cobo, Valter José; Bertini, Giovana [UNESP]; Fransozo, Vivian; Teixeira, Gustavo Monteiro (Cambridge University Press (CUP), 2013)
The relative growths of Persephona lichtensteinii, P. mediterranea, and P. punctata were investigated on the south-eastern Brazilian coast, focusing on differences in the growth rates between immature and mature phases, the onset of morphological sexual maturity, and the breeding seasons of these species. Crabs were collected every two months from January 1991 through to November 1992, from a shrimp fishing boat equipped with two otter-trawl nets. Significant differences in the patterns of body growth were observed between immature and mature phases of all three species. Changes in the growth rates of the chelipeds (males) and abdomen (females) observed for P. lichtensteinii, P. mediterranea, and P. punctata, seem to be related to the puberty moult for both sexes. Males of P. mediterranea and P. punctata reached larger mean sizes of carapace width than females, whereas no difference was recorded for P. lichtensteinii. The body size at which 50% of males attained sexual maturity was also larger in P. mediterranea and P. punctata, and smaller in P. lichtensteinii. The absence of a pronounced sexual dimorphism and the size at the onset of sexual maturity observed only for P. lichtensteinii might be explained by distinct reproductive strategies of males. The presence of ovigerous females during the entire sampling period suggests that all three species have a continuous reproduction pattern at the Ubatuba region. Future studies on the population structure, functional maturity, and mating system should improve the understanding of factors driving the biology and ecology of these species at a subtropical region. © Marine Biological Association of the United Kingdom 2013.
Keywords: morphometry; sexual dimorphism; sexual maturity; south-eastern Brazilian coast; spawning; body size; breeding season; comparative study; crab; growth rate; molt; morphology; subtropical region; Brazil